Piecewise continuous cumulative prospect theory and behavioral financial engineering - Marc Gürtler; Julia Stolpe (Technische Universität Braunschweig, Institut für Finanzwirtschaft, 2011)
We extend the continuous Cumulative Prospect Theory (CPT) by considering piecewise con-tinuous distributions with a finite number of jump discontinuities. Such distributions are rele-vant in practice, for example, within the framework of financial engineering since cash flow distributions of most types of derivatives are only piecewise continuous. In addition, we ex-pand the model with a (piecewise) continuous version of hedonic framing which is, until now, only available in a discrete model setting. We show how to apply the model to a broad class of structured products. Finally, we apply Prospect Theory (PT), CPT, and expected utility theory to a set of different real-life certificates with piecewise continuous and discrete distributions in order to analyze whether there are any significant differences between the theories, and which theory is able to explain the demand behavior of a market participant best. As a result, we recommend the use of the piecewise continuous version of CPT to design products within the framework of behavioral financial engineering.
Keywords: G31; G32; G35; 330; Continuous Cumulative Prospect Theory; Continuous Hedonic Framing; Behavioral Finance; Financial Engineering